2015
DOI: 10.5038/1936-4660.8.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing College Students' Quantitative and Scientific Reasoning: The James Madison University Story

Abstract: Quantitative and scientific reasoning is a critical student learning outcome in higher education. Data are presented for large samples of undergraduate students who were assessed as entering freshmen and then again after completing 45-70 credit hours. Results are presented around four key issues that are central to educational assessment. First, entering freshmen with transfer credits for quantitative and scientific reasoning courses that fulfill general education requirements, on average, score similar to ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The social skills module's curriculum, objective and learning outcome should be the basis for each instrument's items. It is against the law to alter the learning goal, objective, or outcome to comply with the curriculum (Hathcoat et al, 2016).…”
Section: Designmentioning
confidence: 99%
“…The social skills module's curriculum, objective and learning outcome should be the basis for each instrument's items. It is against the law to alter the learning goal, objective, or outcome to comply with the curriculum (Hathcoat et al, 2016).…”
Section: Designmentioning
confidence: 99%
“…For instance, students who have yet to take any courses in a general education program are compared to students who have partially completed or fully completed the program (as shown for our American History and Political Science requirement in Table 4. 1 (See also Hathcoat, Sundre, & Johnston, 2015, Tables 6 and 7.) Furthermore, we consider score differences among students who have completed their requirements elsewhere (e.g., transfer credits, Advanced Placement credits), allowing us to explore the impact of non-JMU coursework.…”
Section: Most Importantly Fall Assessmentmentioning
confidence: 99%
“…Numerous studies have identified general education and/or introductory science courses as venues with the potential to complement the development of numerical skills (e.g., Powell and Leveson 2004, Bray Speth et al 2010, Hester et al 2014, Hathcoat et al 2015. For several decades now, much of the dialogue surrounding the teaching of general education introductory science courses has been focused on instilling "science literacy" (Rutherford andAhlgren 1991, DeBoer 2000).…”
Section: Why General Education Science Courses?mentioning
confidence: 99%